Analisis Penyebab Cacat Pada Kemasan Di Perusahaan Farmasi - Angga Kurniawan; Moch Malgi Alpariz Kadarisman; Eki Yudhistira; Muchammad Fauzi (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
With the increasing era of globalization today, competition in the industrial sector is becoming increasingly fierce and competitive. With the development of modern technology for the better but on the other hand raises problems for the environment. Every business actor who wants to win the competition must pay full attention to the quality of the products or services produced, at a low cost, the right time and quantity, and safe conditions. This study aims to analyze and reduce waste of packaging waste at PT XYZ, a manufacturing company engaged in the manufacture of medicines and vaccines. In the last 7 months, there were 1,906 pcs of defective packaging out of a total of 204,940 pcs used. The defects were caused by mold, misprinted information, faded colors, and lack of glue on the packaging. The methods used in this research are Pareto diagram and fishbone diagram. Pareto diagrams are used to identify dominant product defects, while fishbone diagrams are used to identify the causes of defects. It is expected that the results of this research can help PT XYZ reduce packaging waste and improve the quality of their products. By reducing packaging waste, PT XYZ can also contribute to reducing negative impacts on the environment.